THE RISK FACTORS FOR POSTOPERATIVE OUTCOMES IN NEONATAL CARDIAC SURGERY - Mandzukovska, Hristina (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
In the last three decades a neonatal cardiac surgery has improved the aproach and methods for adequate treatment of complex congenital heart defects. Although we have advances in fetal cardiac imaging and improved perioperative cardiac procedures, the postoperative outcomes in neonates are still present. We present our experience of operated neonates with congenital heart defects in a tertiary referral center, University Clinic for Pediatric Diseases, Neonatal Intensive Care Unit (NICU) in Skopje N. Macedonia. This is a retrospective study including neonates who underwent surgical intervention between January 2013 and December 2015. We analyzed perioperative and postoperative variables, duration of cardiopulmonaly bypass (CPB),  and x-cross of aorta, duration of mechanical ventilation, intensive care unit stay and postoperative complications. Out of a total of 85 children, 15/85 (17.6 %) were neonates; the overall mortality was 1/15% (6.6%).There were 13/15 (86.6%) corrective procedures and 2/15 (13.3%) palliative ones. The mean duration of CPB was 46.6 min.,  duration of x-cross of aorta was 17.5 min. The mean duration of mechanical ventilation was 3.4 days, duration of inotropic support was 4.2 days, and ICU stay 5.8 days. Postoperative complications were confirmed in 3 neonates. Due to adequate cardiac surgery, signicant technological advances, devices and increasing experience in neonatal cardiac surgery we have improved  postoperative outcomes. Keywords: cardiac surgery, neonates, cardiopulmonaly bypass, inotropic support. https://doi.org/10.55302/JMS2141034m